An experimental and theoretical study of the adsorption removal of toluene and chlorobenzene on coconut shell derived carbon. (September 2018) - Zhao, Xiaoyan; Zeng, Xiaolan; Qin, Yu; Li, Xiang; Zhu, Tianle; Tang, Xiaolong
Abstract: The adsorption performance of toluene and chlorobenzene on prepared coconut shell derived carbon (CDC) is investigated and compared with commercial activated carbon (CAC) by experiment and theory calculation. Textural properties of prepared adsorbents are characterized by N2 adsorption, infrared spectra (FT-IR), Raman spectra and X-ray photoelectron spectra (XPS). Adsorption isotherms of toluene and chlorobenzene are obtained and fitted using structure optimizations, Grand Canonical Monte Carlo (GCMC) simulation and thermodynamic models. The results indicate that CDC shows better volatile organic compounds (VOCs) removal performance than CAC, and chlorobenzene is easily adsorbed than toluene. On the aspect of textural characteristics, CDC possesses more micropores ratio and narrower pore size distribution than CAC. Furthermore, amounts of electron-withdrawing carbonyl groups on the CAC surface reduce the electron density of adsorbents, thus weakening the interaction between VOCs and adsorbents. On the aspect of model fitting, the Yoon and Nelson (Y-N) and Dubinin–Astakhov (D-A) models can well describe the dynamic adsorption and the adsorption equilibrium of toluene and chlorobenzene on CDC respectively. It is believed that substituent groups of adsorbates, making the charge distribution deviate, lead to adsorption potentials of chlorobenzene larger than toluene. In general, both the pore structure and the surface property of adsorbents affect the VOCs adsorption behaviors on CDC. Graphical abstract: Image 1 Highlights: Coconut shell derived carbon (CDC) shows better VOCs removal performance than commercial activated carbon (CAC). Chlorobenzene adsorption on CDC exhibits greater affinity (Lennard–Jones potential) than toluene. The electron-withdrawing carbonyl weakens the interaction between VOCs and adsorbents.